Building an alternative 'canon': Milanese publishing and Portuguese-speaking African authors (1961-1976) (Altre Modernità, 2024)
The translation and publication, in Italy, of works by African writers who write in Portuguese begins in the 60s of the 20th century through Milanese publishing. The role of the city of Milan in making the Italian public aware of the works of African writers, who in those years had begun an anti-colonial struggle that would lead to the independence of their respective countries, is certainly not accidental. But which works reach Italy and how? Why do certain publishing houses decide to publish works that in some cases are unpublished in Portuguese? And above all, by whom and how are they translated? In this paper we will try to answer these questions in an attempt to understand the editorial dynamics, the political and personal relationships that made the city of Milan an editorial point of reference in the 60s and 70s of the 20th century.
Keywords: Milanese publishing; Portuguese-speaking Africa; Italian reception; translation